Enhancing a Role and Reference Grammar approach to English motion constructions in a Natural Language Processing environment - Luzondo-Oyón, Alba; Jiménez-Briones, Rocío (Círculo de Lingüística Aplicada a la Comunicación, 2017)
This paper puts forward a finer-grained computational treatment of the English caused-motion construction (e.g. He kicked the ball into the net) within a knowledge base for natural language processing systems called FunGramKB. This computational project is largely based on Role and Reference Grammar (RRG), which is a functional projectionist theory of language. We argue that the RRG-based characterization of the caused-motion construction in FunGramKB is insufficient to account for the semantic and syntactic complexity of realizations such as He walked the dog to the park, I will show you out, or Mac flew Continental to Bush International Airport. Thus, drawing on insights from Constructions Grammars, three minimally distinct transitive motion sub-constructions are formalized within FunGramKB. It is through the inclusion of additional constructional schemas that the machine will be able to capture the various ways in which verbs and constructions interact to yield different input texts.